Perbedaan Nilai Tekanan Darah Antara Operator Produksi Dengan Petugas Laboratorium Pabrik Spunbond Di Balongbendo - Negara, Yohanes Ardian Kapri; Anwari, Farida; Prajawanti, Kadeq Novita; Octifani, Amellya (Media of Health Research, 2023)
Employees who work in their jobs must achieve work goals within a certain period of time. The purpose of the study was to determine the difference in blood pressure values and hemoglobin levels between Production Operators and Laboratory Officers of the Spunbond Factory in Balongbendo. Blood pressure measurement used ABN aneroid tensimeter, while hemoglobin level measurement used easy touch GCHB. The type of research used was quantitative observational analytic with a cross sectional approach. Data analysis using Statistical Package for Social Science (SPSS) includes chi square test, paired sample t-test, and independent sample t-test. Independent sample t-test statistical test obtained p-value> 0.05. Indicates that there is no significant difference between systolic and diastolic blood pressure values before and after working Production Operators with Laboratory Officers. The results of measuring the hemoglobin level of Production Operators, obtained an average hemoglobin level of 15.0 mmHg. While the results of measuring the hemoglobin level of Laboratory Officers obtained an average value of 15.4 mmHg. The results of the independent sample t-test statistical test obtained a p-value of 0.280 or p-value> 0.05. That there is no significant difference in hemoglobin levels between Production Operators and Laboratory Officers.